Risk Assessment of Construction Works in City Square Using Fine Kinney Method - Aslan, Selman (My University, 2022)
Our country, as in other developing countries, tries to minimize work accidents by taking adequate and appropriate measures. It is necessary to adopt and implement occupational health and safety in all work areas, regardless of small or large size. In this context, risk assessments regarding occupational health and safety are vital. Various work accidents may occur in areas such as city squares where human density is high. This study includes the result of an exemplary study by emphasizing the importance of risk assessment in construction works that carried out in areas where people and vehicles are dense, such as busy streets, squares, or boulevards in cities. The results were obtained using Fine Kinney Risk Assessment Method. It was shown that the construction-related risks are vital and have a significant impact on the people not only construction workers but also who have to pass through the construction site.